2017
DOI: 10.1109/tmag.2017.2681045
|View full text |Cite
|
Sign up to set email alerts
|

Domain Decomposition Approach for Efficient Time-Domain Finite-Element Computation of Winding Losses in Electrical Machines

Abstract: Finite element analysis of winding losses in electrical machines can be computationally uneconomical. Computationally lighter methods often place restrictions on the winding configuration or have been used for time-harmonic problems only. This paper proposes a domain decomposition type approach for solving this problem. The slots of the machine are modelled by their impulse response functions and coupled together with the rest of the problem. The method places no restrictions on the winding and naturally inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…A perfect transposition of these is unrealistic, which results in circulating currents that cause the resistive loss to increase. In the case of a random wound 500 kW induction motor, Lehikoinen et al [29] observed that, even with sinusoidal 50 Hz supply, the circulating and eddy current effects together could cause almost 27% increase in resistive losses. Nevertheless, the effect is lower for smaller slot size.…”
Section: Resultsmentioning
confidence: 99%
“…A perfect transposition of these is unrealistic, which results in circulating currents that cause the resistive loss to increase. In the case of a random wound 500 kW induction motor, Lehikoinen et al [29] observed that, even with sinusoidal 50 Hz supply, the circulating and eddy current effects together could cause almost 27% increase in resistive losses. Nevertheless, the effect is lower for smaller slot size.…”
Section: Resultsmentioning
confidence: 99%
“…Content may change prior to final publication. Citation information: DOI 10.1109/ACCESS.2020.3047153, IEEE Access which, by using (5) and 7, becomes:…”
Section: Discrete Constitutive Relationmentioning
confidence: 99%
“…This may occur with local field anisotropies due to, e.g., singular sources, corner singularities, or discontinuous material coefficients. As a further advantage of DDMs, parallel computing can be applied for large sized problems, by sharing among different processors the discretized models of the single components [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…In order to overcome the long computation time and high computation power for FEA analysis, macro-element approach has been applied where the slots of the motor are modeled by their impulse response functions. This method considers all loss components with the same accuracy as the standard FEA, but with speedups 70 to 100 times [56].…”
Section: Copper Loss Modelingmentioning
confidence: 99%